Controllable Phononic Low-Pass Filter via Optomechanical Interactions - Yang, Cheng; Sheng, Jiteng; Wu, Haibin (Frontiers in Physics, 2022)
We present an experimental demonstration of an optically controllable phononic low-pass filter in a multimode optomechanical system. By coupling two spatially separated nanomechanical resonators via optomechanical interactions, the phononic signal below a cutoff frequency can be transferred between mechanical resonators, while the signal above the cutoff frequency is attenuated, which resembles an electronic low-pass filter. Moreover, the cutoff frequency is controllable by tuning the optomechanical interaction via the intracavity field. Our results provide an essential element in phononic circuits and have potential applications for information processing in hybrid quantum systems.